DEVELOPING HUMAN RESOURCES IN THE UZBEKISTAN TEXTILE INDUSTRY THROUGH THE INTEGRATION OF “HALAL” MANAGEMENT AND HR TECHNOLOGIES - Yermatov, Ilmidin Toshmatovich (THE INNOVATION ECONOMY, 2026)
This article proposes a practice-oriented model for accelerated development of human resources in the textile, clothing, and knitwear industries of Uzbekistan based on the simultaneous integration of halal management principles (ethics, responsibility, transparency, and fairness) and modern digital HR technologies (HR information systems, e-recruitment, training systems, HR analytics, and digital time and competency tracking). This institutional framework is supported by the regulatory introduction of the Halol certification procedure by Cabinet of Ministers Resolution No. 57 of February 1, 2025, as well as the international accreditation of UzTest Halal by the Turkish Halal Accreditation Agency (HAK) in 2025. The result is a "Halal - HR + HR - Tech" model and a set of KPIs for the managed improvement of competencies, discipline, engagement, turnover, and export readiness of enterprises.